Classroom in conflict : teaching controversial subjects in a diverse society - Williams, John A., 1935- (SUNY series in philosophy of education., 1994)
"This book transcends recent debates about political correctness to address the underlying problems of teaching controversial subjects in the college and university history classroom. The author criticizes both sides of the debate, rejecting, on the one hand, calls for a uniform, chronological history curriculum and, on the other hand, claims that only ethnic or racial "insiders" are qualified to teach about their communities." "In chapters on colonial, comparative, and African history, Williams applies the concept of "Gandhian truth" to historical subjects, moving through tentative and flexible perspectives to achieve a complex picture of historical episodes. And in chapters on imperialism, nationalism, racism, and the problem of "the other," he discusses the difficult and contingent nature of conceptual language. In the second half of the book, he addresses framing rules of discussion by which sensitive issues can be discussed with diverse audiences, the relationship of American pluralism to a world perspective, and what can be accomplished through an education in pluralism."--Jacket